Training the domestic ferret to discriminate odors associated with wildlife disease. - Glen J Golden (Public Library of Science (PLoS), 2021)
Recent avian influenza infection outbreaks have resulted in global biosecurity and economic concerns. Mallards are asymptomatic for the disease and can potentially spread AI along migratory bird flyways. In a previous study, trained mice correctly discriminated the health status of individual ducks on the basis of fecal odors when feces from post-infection periods were paired with feces from pre-infection periods. Chemical analyses indicated that avian influenza infection was associated with a marked increase of acetoin (3-hydroxy-2-butanone) in feces. In the current study, domesticated male ferrets (Mustela putorius furo) were trained to display a specific conditioned response (i.e. active scratch alert) in response to a marked increase of acetoin in a presentation of an acetoin:1-octen-3-ol solution. Ferrets rapidly generalized this learned response to the odor of irradiated feces from avian influenza infected mallards. These results suggest that a trained mammalian biosensor could be employed in an avian influenza surveillance program.